An introduction to Language Testing's first Virtual Special Issue: Investigating consequences of language test use. (October 2020) - Chapelle, Carol A.
Virtual Special Issues are a new resource for Language Testing readers. The Virtual Special Issues will highlight important topics and trends in the field by curating previously published articles that have contributed to defining important and influential issues, methods, and findings on the topics and trends. This Virtual Special Issue presents selected articles from Language Testing on the topic of the consequences, also referred to as washback and impact, of language assessments and tests. The authors of the articles report their investigations of the social functions of tests in teaching and learning as well as in broader structures for attaining opportunities in society. In particular, the articles encompass the examples of social functions that Messick (1989) identified as potentially important in investigating the validity of test use. They also demonstrate a variety of research methods for the study of the consequences of language assessment use in a range of contexts. They vary in the extent to which they interpret results with respect to validity, but the more recent two articles engage explicitly with issues of consequences and validity. Regardless of the role assumed for consequences in validity arguments, these articles demonstrate the importance of investigating consequences in language testing and illustrate methods for doing so.